Innovations as Response to Failures in Rural Financial Markets - Gilberto M. Llanto; Gabrielle Roanne Lavi\~na (Philippine Institute for Development Studies (PIDS), 2006)
The paper reviews the innovations developed by some financial institutions to meet the challenges of microfinance and rural finance markets. Innovations could be new products and methodologies or refinements to existing practices that are created in response to market inefficiencies and changing demands of a target clientele. Essentially, innovations by financial institutions are not only a means to reach the large unserved poor households but also to provide more and better products and services that could contribute to increasing profitability of the institutions adopting them. The first type is innovations on the financial system which refers to changes in the structure of the financial sector particularly in the legal and regulatory framework. The second type of innovation is institutional innovation which deals with the changes in the structure, organization, and legal form of the institution. Another type of innovation is the process innovation. This refers to the introduction of new business processes leading to increased efficiency or market expansion (most often associated with technological progress). The last type of innovations is products innovation which refers to the introduction of new or modified products or services tailored to the needs of the rural borrowers.
Keywords: 330; microfinance; rural finance; innovation; institutional innovation; products innovation; process innovation; systemic level of innovation; scarcity of collateral; leasing